Research on the supply risk propagation in the global iron ore trade network - Liu, Chao; Zhao, Ting; Wang, Gaoshang; Liu, Shengqian (Frontiers in Earth Science, 2025)
Iron ore serves as a critical resource underpinning global industrialization, extensively utilized in steel production and infrastructure development. Amid increasing complexities in the global economic landscape, risks and uncertainties within iron ore supply chains have intensified, particularly under the influence of geopolitical conflicts and trade protectionism. Leveraging 2023 iron ore trade data, this study constructs a global iron ore trade network using complex network theory and develops a cascading failure model to assess systemic vulnerabilities. Key findings include: ⅰ:The iron ore trade system exhibits a centralized structure dominated by China, Australia, and Brazil, resulting in elevated supply risks. Supply disruptions could propagate crises, potentially disrupting supply chains in over 40% of participating nations.ⅱ:Community 1 (China, Australia, Brazil) accounts for 90% of trade volume and demonstrates heightened susceptibility to cascading failures. In contrast, Community 2 (Canada, Germany, South Africa) mitigates crisis propagation through diversified supply strategies. Enhanced cross-community linkages facilitated by nations like India reduce systemic risks. ⅲ:Critical node failures yield disproportionate impacts: Increasing the risk resilience parameter β from 0.2 to 0.4 reduces cascade magnitude by 62%. While Brazilian disruptions trigger extensive spatial propagation, Australia’s export concentration renders downstream industries more vulnerable to paralysis despite narrower geographic impacts. Based on the evaluation results of the global iron ore trade network, relevant suggestions such as developing emerging supply sources and constructing a deduction system were put forward.